2018
DOI: 10.1016/j.expneurol.2018.04.015
|View full text |Cite
|
Sign up to set email alerts
|

RhoA activation in axotomy-induced neuronal death

Abstract: After spinal cord injury (SCI) in mammals, severed axons fail to regenerate, due to both extrinsic inhibitory factors, e.g., the chondroitin sulfate proteoglycans (CSPGs) and myelin-associated growth inhibitors (MAIs), and a developmental loss of intrinsic growth capacity. The latter is suggested by findings in lamprey that the 18 pairs of individually identified reticulospinal neurons vary greatly in their ability to regenerate their axons through the same spinal cord environment. Moreover, those neurons that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…There also was evidence for transient upregulation of RhoA mRNA in these neurons and for its rapid translocation to the axon tip. After 2 weeks, RhoA expression was reduced selectively in those reticulospinal neurons that did not show caspase activity (Zhang et al, 2018 ).…”
Section: Numerous Intracellular Signals Convey Cspg Inhibition On Neumentioning
confidence: 99%
“…There also was evidence for transient upregulation of RhoA mRNA in these neurons and for its rapid translocation to the axon tip. After 2 weeks, RhoA expression was reduced selectively in those reticulospinal neurons that did not show caspase activity (Zhang et al, 2018 ).…”
Section: Numerous Intracellular Signals Convey Cspg Inhibition On Neumentioning
confidence: 99%
“…RhoA belongs to the Rho family of small GTPases. It circulates between the GDP-bound state and the GTP-bound state, acting as a molecular switch in signal transduction [ 17 ]. In the case of activation, RhoA interacts with downstream effectors such as RhoA-related protein kinase (ROCK), namely, ROCK1 and ROCK-2 [ 18 ], both of which are expressed in most tissues, and ROCK-2 is involved in cytoskeletal reorganization during cell adhesion and contraction.…”
Section: Introductionmentioning
confidence: 99%
“…In the micro-environment of growing neurites, especially in the injured nerve system, there are many kinds of extracellular inhibitory molecules, such as chondroitin sulfate proteoglycans (CSPGs), myelin-associated glycoprotein (MAG), Lingo-1, Nogo, oligodendrocyte-myelin glycoprotein (OMgp), and so on [11][12][13]. Existing evidence has suggested that the small GTPase RhoA subfamily (RhoA) is an intracellular convergence point for most extracellular inhibitory signals [14][15][16]. Previous studies have reported that the mechanism of RhoA action as a pivotal inhibitory signaling pathway in developing and regenerating neurons can be attributed to actin microfilament rearrangements, since RhoA facilitates the formation of actin stress fibers and focal adhesions through its downstream effector, Rho-associated coiled coil-forming kinase (ROCK) [15,17].…”
Section: Introductionmentioning
confidence: 99%